THE URDU VERSION OF THE SAFETY ATTITUDE QUESTIONNAIRE (SAQ) FOR INPATIENT SETTINGS IN PAKISTAN: PSYCHOMETRIC PROPERTIES AND BASELINE DATA - Khan, Hammad Muhammad; Fazal, Muhammad Zeeshan; Shah, Mohsin Ali; Ali, Owais Muhammad; Afridi, Suleman Khan; Ahmad, Hasnain Syed; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: This study aimed to test the psychometric properties of the Urdu version of the Safety Attitudes Questionnaire for inpatient settings in Pakistan. Methods: The SAQ short form (inpatient version) was translated with the back-translation technique into Urdu. The SAQ-Urdu was administered in three teaching hospitals in Pakistan to a sample of 483 front line healthcare personnel from August 2016 through December 2017. Confirmatory factor analysis was performed to test the factor structure of the responses. Cronbach’s alphas and correlation coefficients were computed. Mean and percentage agreement scores for items were reported. Results: The response rate was 75%. Goodness-of-fit indices from the confirmatory factor analysis showed a reasonable model fit (Ï‡2=213.27, df=125, p<0.001; CFI 0.94, RMSEA 0.044). Cronbach’s alphas of survey factors (teamwork climate, safety climate, job satisfaction, perceptions of management, and working conditions) ranged from 0.71 to 0.87. In terms of mean percentage agreement scores, substantial variability was found at the clinical unit level. Conclusion: The Urdu version of the SAQ showed satisfactory internal psychometric properties. The attitudes around patient safety considerably vary and indicate a need for improvement. Keywords: Patient safety; Healthcare; Pakistan; Safety culture